Hematology and biochemistry of Colossoma macropomum co-infected with Aeromonas hydrophila and monogenean Anacanthorus spathulatus after treatment with seed extract of Bixa orellana - Andrade, Jaqueline Inês Alves de; Jerônimo, Gabriela Tomas; Nunez, C. V.; Santos, Raphael Brito dos; Araújo, Jandiara Kelly Oliveira; Ruiz, Maria Luiza; Mouriño, José Luiz Pedreira; Santos, Vanessa Neves Carvalho; Martins, Maurício Laterça (Aquaculture, 2018)
This study evaluated the use in vitro and in vivo of Bixa orellana seed extracts on the hematological and biochemical parameters of Colossoma macropomum co-infected with bacterium and monogenean, Anacanthorus spathulatus. The extract presented antimicrobial and antiparasitic activity in vitro against the pathogens. Fish supported the toxicity test and in vivo assay used 180 fish distributed in six treatments in triplicate: non-parasitized fish non-injected with A. hydrophila; non-parasitized fish non-injected exposed to acetone 0.2%; parasitized fish injected non-treated with the extract; parasitized fish injected treated with 125 μg mL−1 of extract in 2 h bath for two consecutive days; parasitized fish injected treated with 250 μg mL−1 of extract in 2 h bath for two consecutive days; parasitized fish injected treated with 125 μg mL−1 of extract for 12 h. After last bath, the fish were examined. Acetonic extract showed minimal inhibitory concentration of 125 μg mL−1 against A. hydrophila in the in vitro test and 100% efficacy against monogenean with therapeutic baths in relation to control non-treated in the in vivo test. Aeromonas hydrophila infection did not cause mortality. The gross pathology analysis showed ascites and hemorrhagic liver, kidney and spleen. Increased hemoglobin concentration, mean corpuscular hemoglobin concentration and total number of erythrocytes was followed by a decrease in hematocrit percentage in non-treated fish compared to basal group. Lymphocytes from fish in the control group were higher than in the other groups. Glucose was higher in treated fish than that found in those of basal and control. The results demonstrated that B. orellana bath was an effective alternative to treat fish diseases. © 2018 Elsevier B.V.
Keywords: Anti-microbial Activity; Aquaculture; Assay; Bacterial Disease; Bacterium; Bioactivity; Biochemistry; Chemical Composition; Disease Treatment; Finfish; Hematology; Parasitism; Plant Extract; Seed; Shrub; Toxicity Test; Aeromonas Hydrophila; Bacteria (microorganisms); Bixa Orellana; Colossoma Macropomum; Monogenea